Implementation of the Superior Waste Concept for Rice Husk: Managing Rice Husk Waste Into Biochar and Charcoal Briquettes as Economic Products - Nasution, Nur Aisyah; Pakpahan, Agrevina; Sitompul, Tia Angelina; Napitu, Rizal Aprianto; Sirait, Jhonatan Brizzy; Rahman, Ramadhani Arief (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to apply the principles of Superior Waste Management by processing rice husks into products that are economically valuable and environmentally friendly, such as charcoal briquettes and biochar. This research was conducted in Senaning Village, Jambi, with an approach that involved community participation through training. The research results show that briquettes made from rice husks have high calorific value and low water content, making them very suitable for use as an alternative fuel source. Apart from that, the biochar produced is also able to improve soil quality and store carbon, which provides important benefits for the agricultural sector and reduces the impact of climate change. This program not only helps reduce pollution, but also opens up additional economic opportunities for the community